IntegrationThe Perspective of Time Management Theory and Role Strain Theory in the Correlational Study of Time Management, Role Conflict and Academic Achievement of Prior Learning Recognition (RPL) Students of Toraja Christian University of Indonesia - Rati Pundissing; Chrismesi Pagiu; Nurlela (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the relationship between time management and academic achievement of Recognition of Prior Learning (RPL) students at the Indonesian Christian University of Toraja, and to determine whether role conflict moderates the relationship between time management and academic achievement from the perspective of time management theory and role strain theory. This study uses a quantitative approach with a moderated regression analysis method (MRA). The population in this study were all RPL students at the Indonesian Christian University of Toraja, with a sampling technique using saturated sampling. Data were collected through questionnaires distributed to respondents and analyzed using the SEM-Smart PLS program. The results showed that time management had a positive and significant effect on academic achievement of RPL students with a path coefficient of 0.607, T of 3.769, and a p-value of 0.000. This means that the better the student's ability to manage time, the higher the academic achievement achieved. However, role conflict did not act as a moderating variable in the relationship between time management and academic achievement with a path coefficient of 0.180, T of 1.289, and a p-value of 0.197. Thus, the level of role conflict experienced by students does not change the strength or weakness of the influence of time management on academic achievement